Real-time monitoring system for passive energy-saving houses in the internet of things environment. Issue 3 (4th April 2020) - Zheng, Huikai
The real-time monitoring system can improve the management of passive energy-saving houses. Therefore, this paper proposes a real-time monitoring system for passive energy-saving houses in the internet of things. Construct the overall framework of the system, use DSP integrated signal processor to process real-time information; select PCI9054 bus as output bus transmission mode, control the local bus through PCI, use the transceiver conversion module to analyse the monitoring information in real time; use ADO.NET component library Interact with the database to realise IoT management and control of monitoring information, and implement system software design by wavelet transform algorithm. The simulation results show that the designed system has a monitoring delay of only 2s, and the overall stability is strong. It can process the monitoring information of energy-saving houses in real time.